Phenomenon of Covert Prostitution Practices : Case Study of Spa Plus Therapist Practices in Bandung City - Sisca Lestari; Syafruddin (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the practice of covert prostitution that is developing in Bandung City with a focus on male-only spas that provide sexual services. Although the government has made efforts to control it, including closing the Saritem localization, prostitution continues to exist in a more hidden and organized form. Using qualitative methods, data were collected through field observations and in-depth interviews with informants who have direct experience in this business. The results of the study show that spas are used as a cover for prostitution businesses, by utilizing spa business licenses from the tourism office. Therapists are recruited through agents, and spas are designed with comfortable facilities and strategic locations for easy access by customers, especially tourists. This phenomenon shows a shift in the pattern of prostitution from open to covert, with the main drivers being market demand and profit motives from business owners. This study recommends the need to review business license regulations and strengthen supervision of licensed entertainment venues